NANOTOXICOLOGY AND BIOINTERACTION ASSESSMENT OF BIOMEDICAL NANOMATERIALS - Ivan Dimitrov; Maria Ivanova; Muntasir Muntasir (Journal of Biomedical and Techno Nanomaterials, 2026)
Biomedical nanomaterials have garnered significant attention for their potential applications in medical diagnostics, drug delivery, and therapeutic interventions. However, concerns regarding their toxicity and biointeraction with biological systems remain largely unaddressed. Understanding the safety and biological interactions of these materials is crucial for ensuring their efficacy and safety in clinical settings. The aim of this study was to assess the nanotoxicological properties of biomedical nanomaterials and their interactions with biological systems. The research focused on evaluating the cytotoxicity, genotoxicity, and immunotoxicity of various nanomaterials commonly used in biomedical applications. A combination of in vitro and in vivo assays was employed to assess the toxicological profile of biomedical nanomaterials. These included cell viability tests, oxidative stress analysis, DNA damage assays, and immune response evaluations. The interactions between nanomaterials and cellular components were also examined using advanced imaging and spectroscopy techniques. The findings indicated that the toxicity of nanomaterials varied depending on their size, surface charge, and composition. Certain nanomaterials demonstrated significant cytotoxic and genotoxic effects, while others showed minimal toxicity. The biointeractions were also influenced by the concentration and exposure duration. The study underscores the need for comprehensive toxicity assessments of biomedical nanomaterials to ensure their safe application in medical technologies. Further research is required to optimize their safety profiles for clinical use.